Antarctic krill habitat suitability variation in the Southern Ocean over 20 years - Tan, Yiyang; Bai, Yan (Frontiers in Marine Science, 2025)
Antarctic krill (Euphausia superba) is a key species that sustains the biodiversity of the Southern Ocean and is a protected and restricted fishing target in this region. Considering the significant impacts of climate change on the ecological environment of the Southern Ocean, it is critical to understand the long-term spatio-temporal habitat distribution of Antarctic krill. This study integrates remote sensing and reanalysis data with Antarctic krill survey records to evaluate krill habitat suitability in the Southern Ocean. A novel habitat suitability model was developed using phytoplankton phenology and sea ice dynamics as key timing parameters, employing the Categorical Boosting (CatBoost) algorithm. This is the first time interannual variation in krill habitat distribution, spanning over 20 years (1997–2019), has been analyzed in relation to environmental parameters. Results show that the ice-free period in the Amundsen Sea has extended annually, while phytoplankton blooms have occurred earlier, lasted longer, and exhibited increasing chlorophyll a concentration (CHL), particularly in coastal regions. Additionally, the CatBoost model outperformed traditional species distribution models (SDMs) in handling large-scale presence-absence data (GCV = 0.16), demonstrating that bloom peak CHL and sea ice retreat timing are more effective indicators of krill habitat suitability than single-time environmental parameters. Based on long-term changes in highly suitable habitat areas for Antarctic krill and synchronized trends with the Southern Annular Mode (SAM) index, the overall area of suitable habitat for Antarctic krill in the Prydz sector has declined, likely linked to surface cooling caused by climate change. In contrast, the coastal region of the Atlantic sector, particularly the Western Antarctic Peninsula, a rapid warming area, has experienced an increase in krill habitat suitability. However, habitat suitability in the Weddell Sea has shown a marked decrease. Although climate change has produced mixed effects on krill habitats due to the varying responses of krill different life stages to environmental parameters, this study overall highlights a degradation of krill habitat in the Southern Ocean over the past two decades. These findings provide new insights into Antarctic krill habitat modeling and offer a long-term perspective on the climate change impacts, emphasizing the need for future under-ice investigations.